1985
DOI: 10.1002/1097-0142(19850815)56:4<768::aid-cncr2820560412>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphoma of Waldeyer's ring and nasal cavity. Clinical and immunologic aspects

Abstract: Twenty-nine cases of non-Hodgkin's lymphoma of Waldeyer's ring (W-NHL) and nasal cavity or paranasal sinus (N-NHL) were studied for tumor-surface marker phenotype and histopathologic correlation with clinical features. Immunostaining procedures on tissue sections by using xenoantisera and monoclonal antibodies to human B- and T-cells enabled the authors to demonstrate precise surface marker phenotypes of tumor cells and, moreover, the histologic localization of normal or neoplastic B- and T-cells in preserving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 25 publications
2
39
1
2
Order By: Relevance
“…Other studies have also found size and stage of disease to be poor prognostic factors. 6,7,21 In our current series, WHO performance score 2, the presence of B-symptoms, tumor bulk [7 cm, and higher Ann Arbor stage were associated with inferior outcome (Table 2). On multivariate analysis, a performance score 2 and the presence of 'B' symptoms retained their poor prognostic significance (Table 3).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Other studies have also found size and stage of disease to be poor prognostic factors. 6,7,21 In our current series, WHO performance score 2, the presence of B-symptoms, tumor bulk [7 cm, and higher Ann Arbor stage were associated with inferior outcome (Table 2). On multivariate analysis, a performance score 2 and the presence of 'B' symptoms retained their poor prognostic significance (Table 3).…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, a majority of these patients (60%-70%) present with early stage (stages I and II) disease. 6,7 Gao et al 19 reported 69.6% of their patients to have localized (stage I or II) disease, whereas in the series by Mohammadianpanah et al 17 18% of patients had stage I and 67% had stage II disease. From January 1990 to December 2002, 148 patients with NHL involving the tonsil were treated at the Tata Memorial Hospital, Mumbai.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the demonstration of the EBV/C3d receptor on cells from the stratified squamous epithelium of the oropharynx (Young et al, 1986;Talacko et al, 1991), which also covers the tonsils, has lead to the current hypothesis that this epithelium plays an important role in EBV persistence and the pathogenesis of B cell tumours (Allday & Crawford, 1988). In view of these findings, the observation of human palatine tonsils as a potential source of the EBVassociated lymphomas reported here is of particular importance.…”
Section: Discussionmentioning
confidence: 70%
“…Тонзиларни лимфоми имају добру прогнозу 5 . Већина ових пацијената има локализовану болест 6,7,8,9 , стадијум 1 или 2. Код пацијената са раним стадијумом болести без обимних маса, петогодишње преживљавање је 65%-85% 3,8,10,11 .…”
Section: уводunclassified